Pengaruh Lingkungan Pondok Pesantren Terhadap Mutu Pembelajaran Pendidikan Agama Islam - Isa, Abdullah; Nasiri, Nasiri; Mahmudah, Mila (Jurnal Keislaman, 2024)
This research discusses the influence of the Pondok Pesantrena environment on the quality of Islamic Religious Education learning in the MA X Nurul Khoir Surabaya class. This research uses a quantitative approach and a qualitative approach at the same time. The results of the research show that the environmental intensity of the Islamic Boarding School in the MA X Nurul Khoir Surabaya class is included in the good level category. The influence between the Pondok Pesantrena environment and the quality of Islamic Religious Education learning in the Calss X MA X Nurul Khoir Surabaya can be concluded that there is a correlation. In general, the Islamic boarding school environment in class X MA Nurul Khoir Surabaya is in good condition. The quality of Islamic Religious Education learning is included in the good level category. Therefore, the quality of Islamic religious education learning will also have a good impact as long as the Islamic boarding school environment is in the good category.